Reference Intervals for Biochemical Analytes in Clinically Healthy Adult Lusitano Horses - Maria João Pires; Mário Cotovio; Felisbina Queiroga; Carlos André Pires; Ana C. Silvestre-Ferreira (Veterinary Sciences, 2025)
To date, serum biochemical analytes reference intervals (RIs) in Lusitano horses have not been studied. This study aimed to establish the RIs for biochemical analytes following the American Society of Veterinary Clinical Pathology guidelines and to compare them with the general equine population’s RIs. Blood samples were collected from 76 clinically healthy adult Lusitano horses, and RIs of 22 biochemical variables were determined using Reference Value Advisor software. Lusitano horse-specific RIs are proposed for the following variables: total protein (3.9–7.0 g/dL), albumin (2.5–3.8 g/dL), globulin (1.1–3.7 g/dL), total bilirubin (1.0–5.6 mg/dL), direct bilirubin (0.09–0.68 mg/dL), indirect bilirubin (0.7–5.2 mg/dL), urea (21.0–38.9 mg/dL), creatinine (0.9–2.0 mg/dL), aspartate aminotransferase (150.7–345.1 IU/L), alkaline phosphatase (60.7–227.4 IU/L), lactate dehydrogenase (247.6–959.0 IU/L), glucose (75.5–131.5 mg/dL), cholesterol (58.6–125.2 mg/dL), sodium (129.0–154.9 mmol/L), phosphorus (1.8–4.5 mmol/L), chloride (90.3–107.0 mmol/L), and calcium (8.9–12.6 mg/dL). Different RIs were identified for healthy adult Lusitano horses for 17/22 serum biochemical analytes tested, emphasizing the need for breed-specific RIs to prevent misinterpretation of laboratory results.